Modelos paramétricos simples e causais para cabos de cobre apropriados para caracterização de enlaces em sistemas G.fast - NUNES, Diogo Lobato Acatauassú (Universidade Federal do Pará, 2015)
The G.fast is a new standard from the International Telecommunication Union that targets 1 Gb/s over short copper loops, using frequencies up to 212 MHz. This new technology requires accurate parametric cable models for simulation, design and performance evaluation tests. Most existing copper cable models were designed for the VDSL spectra - i.e., frequencies up to 30 MHz - and adopt assumptions that are violated when the frequency range is extended to G.fast frequencies. This thesis presents new simple and causal cable models that are able to accurately characterize copper loops composed by single or multiple segments, in both frequency and time domains. Results using G.fast topologies show that, besides being accurate, the new models are attractive due to their low computational cost and closed-form expressions for fitting their parameters to measurement data.